The effectiveness of a proposed program based on positive thinking skills in literary awareness among fifth-grade literary students - Al-Mousawi, Ali Hassan Muhaisin; Al-Tamimi, Dia Abdullah Ahmed (Al-Adab Journal, 2021)
This research aims at:Building a program to develop positive thinking skills for literary fifth graders.2. Know the effectiveness of the proposed program for positive thinking skills and their relationship to development of literary awareness.To achieve the goal of the research, the researcher developed an educational program include educational objectives, content and teaching methods, activities appropriate accompaniment and teaching aids for the program implementation. The researcher check validity by presenting it to the group of arbitrators and experts.To find out the effectiveness of the proposed program the researcher depends an experimental design with tuning part, which is the design of the control group with the before and after test.The Researcher select a sample consist of (60) students from fifth grade literature in Al- Rafidain and Al-Nahrawan schools for Boys, the researcher taught the proposed program to the sample by himself, and prepare two tests the first used to measure positive thinking skills and their relationship to reading comprehension included 24 items distributed on the major and minor skills in the search.The experiment lasted an entire semester, and after analyzing the data using a t-test for two independent samples and interrelated the study finding out the following results:First: there is statistically significant difference between the average grade's students in the two sets of research reading comprehension in post-test, for the experimental group at the level of significance (0.001).Second: There is a statistically significant difference between the average scores of students of the experimental group that are taught according to the proposed program and the average scores of students of the control group that are taught according to the traditional method of post-test for literary awareness, and in favor of the experimental group at the level of significance (0.001).Third: There is a statistically significant difference between the average of students' scores in the reading comprehension test, and in favor of the experimental group (post) at the significance level (0.001).In light of the research results, the researcher concluded a number of conclusions, including:The proposed program has proven effective in reading comprehension for fifth-grade literary students. Therefore, learning positive thinking skills is not an inherited talent or an innate queen. All individuals can possess positive thinking skills if the capabilities and the appropriate programs for training on them are available.Training procedures, including teacher modeling and learner practice, have helped students in the practical application of each skill better, giving students a great deal of responsibility for their learning process, giving them confidence in themselves, and making them more positive in educational situations.The researcher suggested conducting a number of studies to complement this study, including:Building a suggested program for developing positive thinking skills in other studying stages (elementary, middle and university levels).Evaluating the levels of students of the different educational levels in positive thinking skills.